Anti-SARS-CoV-2 Activity of Andrographis paniculata (Burm.f.) Nees Extract via Inhibition of Spike-mediated Syncytia Formation in HEK293T Cell Model - Prasetyaningrum, Pekik Wiji; Kastian, Ria Fajarwati; Novianti, Metta; Santoso, Adi; Septisetyani, Endah Puji (HAYATI Journal of Biosciences, 2024)
The resurgence of COVID-19 endemic cases at the end of 2023 has underscored the need for effective treatments. Some severe cases of COVID-19 are often characterized by the formation of multinucleated syncytial pneumocytes in the lungs. Therefore, our study aimed to explore the potential of Andrographis paniculata (Burm. f) Nees as an antivirus against SARS-CoV-2, which involves syncitia formation. We utilized the non-toxic concentrations of A. paniculata extract on HEK293T cells determined by MTT assay, which were 1 μg/ml (cell viability 97.96%) and 10 μg/ml (cell viability 95.24%) for further assays. First, we conducted a pseudovirus cellular entry assay as a model of SARS-CoV-2 infection in HEK293T cells expressing hACE2/TMPRSS2. The HEK293T cells were co-transfected with plasmids expressing hACE2 and TMPRSS2, then infected with pseudotyped spike*∆G-GFP rVSV with or without A. paniculata extract. The internalized pseudovirus would trigger GFP expression as a reporter of the infected cells. Next, we performed a syncytia assay by transfecting HEK293T cells with hACE2, TMPRSS2, and SARS-CoV-2 spike expression vectors to induce syncytia formation as a model of intercellular viral transmission. As the results, 10 μg/mL of the extract significantly lowered the number of SARS-CoV-2 pseudovirus-infected cells by 54.69% (P = 0.02) and spike-mediated syncytia formation by 42.39% (P<0.001). In conclusion, our results suggested that A. paniculata has a potential antiviral activity against SARS-CoV-2 by hindering virus infection and cell-to-cell transmission.